Efecto del financiamiento bancario en la gestión económica de las mypes del Sector Minero de la provincia de Pataz. - Garcia Barriga, Julio César (2016)
The purpose of the research was to confirm which bank financing directly affects the economic management of MSEs in the mining sector in the province of Pataz and that this tool is convenient and useful for more liquidity and increase working capital. The problem was investigated What is the effect of bank financing in the financial management of MSEs Mining Sector of the Province of Pataz? The hypothesis was made that the bank financing has a direct impact on the economic management of MSEs Mining Sector of the Province of Pataz. The study population and the sample was Mining Exploitation and Investment Company Hnos. Sanchez SAC Pataz province, being this representative and appropriate. The method used was the descriptive - deductive and techniques used were document analysis and interview. The most important and momentous results were that the procedure is established for bank financing as MSE, which also correctly applied the International Financial Reporting Standards for MSEs (Section 25 - Borrowing Costs). An important and relevant conclusion is that bank financing for these businesses is a very useful tool and help much to increase liquidity and not risk their own capital, increasing its working capital to expand its activities and hence profits.